The Collections of Miraculous Stories on the Buddhāvataṃsaka-sūtra - Liu, Jing (Távol-keleti Tanulmányok, 2025)
This paper examines the three primary Chinese translations of the Buddhāvataṃsaka-sūtra— an extensive Mahāyāna text foundational to the Huayan School during the Sui and Tang Dynasties. This study provides a comprehensive introduction to each translation, tracing its dissemination across China, and further investigates the contributions and legacy of the five patriarchs of the Huayan School. As Buddhism became increasingly secular and accessible, there was a significant rise in literary creativity, notably in the form of miraculous story collections that aided in the propagation of Buddhist beliefs among the general populace. These narratives, often embellished with supernatural elements, were crafted to demonstrate the efficacy of Buddhist practice, with the aim of fostering faith and devotion. Known as ’stimulus-response’ stories (ganying 感應), these accounts illustrate the power of Buddhist practice through the depiction of miraculous events. This paper reviews nine key collections associated with the Huayan jing, including: Record of the Transmission of the Avataṃsaka-sūtra (Huayanjing Zhuanji 華嚴經傳記), Account of Stimuli and Responses Related to the Avataṃsaka-sūtra (Dafangguang fo huayanjing ganying zhuan 大方廣佛華嚴經感應傳), Account of the Search for the Profundities of the Avataṃsaka-sūtra (Huayanjing tanxuan ji 華嚴經探玄記), Commentary on the Avataṃsaka-sūtra (Dafangguang fo huayanjing shu 大方廣佛華嚴經疏), Sub-commentary on the Avataṃsaka-sūtra (Dafangguang fo huayan sui shu yanyi chao 大方廣佛華嚴經隨疏演義抄), Account of Chengguan’s Commentary on the Avataṃsaka-sūtra (Huayan xuantan huixuan ji 華嚴懸談會玄記), Short Record of Accounts of Stimuli and Responses Related to the Avataṃsaka-sūtra (Dafangguang fo huayanjing ganying lüeji 大方廣佛華嚴經感應略記), and Causes of Stimuli and Response Related to the Avataṃsaka-sūtra (Huayanjing ganying yuanqi zhuan 華嚴經感應緣起傳), as well as the Chronological Account of the Efficacies of the Avataṃsaka-sūtra (Lichao huayanjing chiyan ji 歷朝華 嚴經持驗紀). Through this analysis, the paper aims to deepen understanding of the Avataṃsaka Sūtra, its miraculous stories, and the collections that preserved these narratives, enriching appreciation for its impact on Chinese Buddhism.